2021
DOI: 10.1111/jsap.13297
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and influencers of North American dog‐owners surrounding antimicrobials and antimicrobial stewardship

Abstract: Objectives To quantify the individual influences of antimicrobial cost, method of administration and drug importance in human medicine on dog‐owner antimicrobial preference, and determine knowledge, attitudes and influencers of dog‐owners surrounding antimicrobials and antimicrobial stewardship. Materials and Methods Data were collected through an online survey targeting three dog‐owner participant groups. These consisted of individuals residing in: (1) Canada, (2) USA and (3) any country recruited through an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 41 publications
3
31
2
Order By: Relevance
“…The relatively low priority owners placed on cost is seemingly at odds with the findings of a recent survey of dog owners from North America [ 20 ], which found that low cost of treatment was more important (accounting for 47% of dog owner preferences) than ease (31% of owner preferences). However, the strong signal that convenience is less important to owners than effectiveness is also reflected in a cat owner survey in the UK, in which 88% of owners indicated that getting the most appropriate antibiotic was more important than ease of administration [ 21 ].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The relatively low priority owners placed on cost is seemingly at odds with the findings of a recent survey of dog owners from North America [ 20 ], which found that low cost of treatment was more important (accounting for 47% of dog owner preferences) than ease (31% of owner preferences). However, the strong signal that convenience is less important to owners than effectiveness is also reflected in a cat owner survey in the UK, in which 88% of owners indicated that getting the most appropriate antibiotic was more important than ease of administration [ 21 ].…”
Section: Discussionmentioning
confidence: 95%
“…Our results show that owners prefer arguments centered on the health of their pet, the possibility of their pet experiencing direct adverse effects from the antibiotic and the possibility of ‘superbugs’ developing in their pet, and effectiveness over arguments around relative cost, public health or veterinary prescribing guidelines. Arguing for an antimicrobial because it is of lower importance to human and animal medicine is also unlikely to be helpful; most dog owners in the North American study actually indicated a preference for their dog to receive high-importance antimicrobials over lower-importance antimicrobials [ 20 ]. Instead, framing a lower-importance antibiotic as a safer and more effective choice for their pet is likely to be more compelling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous surveys of pet owners have provided conflicting evidence on willingness to spend money on veterinary care. [8][9][10] Compliance with treatment is a concern in both human and veterinary medicine. 11 One study on dog owners indicated a preference for not administering oral medications.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous surveys of pet owners have provided conflicting evidence on willingness to spend money on veterinary care. 8 10 …”
Section: Introductionmentioning
confidence: 99%